Analisis Pengaruh Kualitas Pelayaran terhadap Kepuasan Pelanggan Jasa Kapal PT PNEP di Industri Galangan Kapal Menggunakan Metode SEM (Structural Equation Modelling) - Dei Oktavira; Asep Mohamad Noor (Yayasan Literasi Sains Indonesia, 2026)
The Indonesian maritime service industry operates within a project-based ecosystem characterized by high operational complexity and contractual performance demands, positioning service quality as a strategic determinant of customer satisfaction. This study aims to analyze the influence of administrative performance, project performance, marketing management, and price perception on customer satisfaction at PT PNEP using a Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. This research employed a quantitative design with a positivistic paradigm and surveyed 96 customers who completed contracts during 2020–2022. Data were collected through structured questionnaires comprising 29 indicators measured on a five-point Likert scale and analyzed using SmartPLS version 4. The measurement model demonstrated adequate convergent and discriminant validity, with all retained indicators achieving loading factors above 0.70 and AVE values exceeding 0.50. The structural model indicated that project performance and price perception had positive and significant effects on customer satisfaction, while administrative performance and marketing management were not statistically significant. Price perception emerged as the most dominant determinant (β = 0.517; p < 0.001), and the model explained 63.1% of the variance in customer satisfaction (R² = 0.631). In conclusion, customer satisfaction in project-based maritime services is primarily driven by core value factors, particularly project performance and perceived price fairness.